Analisis manfaat laporan keuangan berbasis AKRUAL dalam pengambilan keputusan di Pemerintah Kabupaten Bantaeng - Alrahim, Abul A’la; Wibowo, Puji (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2022)
This study aims to determine the use of information generated from the accrual-based local government reports of Bantaeng Regency by its users. The analytical method used is a qualitative method. Data collection through interviews, questionnaires and document review. Then for the analysis of data from interviews and document review using an interactive model of analysis, while the questionnaire data were analyzed using descriptive statistics. The results of the study show that users use accrual-based information on Local Government Financial Statements in the process of making decisions. The Utilization of each financial report for different decision-making, namely: first, the balance sheet is useful for decision making in the procurement of resources for the next period as well as the management of assets and liabilities of local governments; The second LRA is useful in making decisions to assess the level of budget absorption and evaluation of materials for the next period; the three LO is useful in decision making in assisting the budgeting process, understanding government policies and strategic plans; lastly, CaLK is useful in decision making in helping to explain the calculation of accounts on the face of the financial sheet in order to reduce risk for reports in decision making